The Factors Affecting Stunting on Toddlers in Coastal Areas - Dwining Handayani; Erik Kusuma; Helda Puspitasari; Ayu Dewi Nastiti (Universitas Aisyah Pringsewu, 2022)
Stunting is a physical growth disorder characterized by a decrease in the speed of growth that occurs due to a lack of nutritional intake in children in the first 1000 days of life. The prevalence of stunting in Pasuruan Regency is high, at 22.5%. The area with the highest prevalence of stunting is the coastal area. This study aims to determine the factors that cause stunting in children under five in the coastal area of Pasuruan. The results showed that from the 17 variables analyzed, 6 factors have formed that influence the incidence of stunting in coastal areas, including high parental education factors, history of infectious diseases, economy, breastfeeding, family structure and nutrition of pregnant women. The results showed that from the 17 variables analyzed, 6 factors have formed that influence the incidence of stunting in coastal areas, including high parental education factors, history of infectious diseases, economy, breastfeeding, family structure and nutrition of pregnant women. The results showed that from the 17 variables analyzed, 6 factors have formed that influence the incidence of stunting in coastal areas, including high parental education factors, history of infectious diseases, economy, breastfeeding, family structure and nutrition of pregnant women. An integrated and multi-sectoral program is needed to increase family income, family knowledge related to balanced nutrition and the growth and development of toddlers to reduce the incidence of stunting. Abstrak: Stunting merupakan gangguan pertumbuhan fisik yang ditandai dengan penurunan kecepatan pertumbuhan yang terjadi karena kurangnya asupan gizi pada anak dalam 1000 hari pertama kehidupan. Prevalensi stunting di Kabupaten Pasuruan tergolong tinggi, yaitu 22,5%. Wilayah dengan prevalensi stunting tertinggi adalah wilayah pesisir. Tujuan penelitian ini adalah mengetahui faktor-faktor penyebab stunting pada balita di daerah pesisir Kabupaten Pasuruan. Jenis penelitian ini adalah studi analitik observasional dengan desain case control. Sampel dalam penelitian ini adalah balita stunting berusia 24 - 60 bulan sebanyak 51 orang yang dipilih dengan teknik quota sampling. Penelitian dilaksanakan pada bulan Mei-Agustus 2021. Instrumen yang digunakan adalah kuesioner dan observasi. Analisis data menggunakan uji KMO dan Bartlett's Test. Hasil penelitian menunjukkan dari 17 variabel yang dianalisis terbentuk 6 faktor yang mempengaruhi kejadian stunting di wilayah pesisir antara lain tinggi faktor pendidikan orang tua, riwayat penyakit infeksi, ekonomi, pemberian ASI, struktur keluarga dan nutrisi ibu hamil. Perlu program yang terintegrasi dan multisektoral untuk meningkatkan pendapatan keluarga, pengetahuan keluarga terkait gizi seimbang dan tumbuh kembang balita untuk mengurangi kejadian stunting.